2011
DOI: 10.1007/s00726-011-1169-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of slow-release β-alanine tablets on absorption kinetics and paresthesia

Abstract: Oral β-alanine (βA) doses larger than 800 mg commonly result in unpleasant sensory symptoms (paresthesia). However, the association of form (pure vs. slow-release) with side-effects has not been fully described. The aim of this single-blinded, randomized three-arm clinical trial was to compare plasma kinetics and symptoms following βA bolus administration in solution or in slow-release tablet form. Eleven healthy adults ingested 1.6 g of a pure βA reference solution (REF), 1.6 g in slow-release βA tablets (TAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 31 publications
7
78
0
3
Order By: Relevance
“…e sustained-release formulation of β-alanine used in the present study has been shown to reduce the symptoms of paraesthesia often associated with individual doses of β-alanine administered as free powder 22 . In this study, none of the participants reported any feelings of paraesthesia, and we are con dent that the integrity of the double blinding was maintained.…”
Section: Methodsmentioning
confidence: 88%
“…e sustained-release formulation of β-alanine used in the present study has been shown to reduce the symptoms of paraesthesia often associated with individual doses of β-alanine administered as free powder 22 . In this study, none of the participants reported any feelings of paraesthesia, and we are con dent that the integrity of the double blinding was maintained.…”
Section: Methodsmentioning
confidence: 88%
“…It has previously been demonstrated that this slow-release tablet of BA results in a blunting of peak plasma BA with similar area under the curve compared to pure BA (Decombaz et al 2011;Harris et al 2008). This slow-release BA still reaches plasma concentrations above the BA transporter K m of *40 lM (Bakardjiev and Bauer 1994) and thus would be hypothesized to be effective for muscle carnosine synthesis.…”
Section: Discussionmentioning
confidence: 93%
“…1). These questionnaires included a body surface symptoms score (SSS), profile of mood states (POMS) and a state anxiety inventory (SAI), and are fully described by Decombaz et al (2011). The flushing symptoms questionnaire (FSQ) was developed specifically for this study, and was a 10-question retrospective questionnaire focusing on any unusual skin or paresthesia symptoms, and the intensity and duration of symptoms, in the previous 24 h. Questions on ''warmth'', ''redness'', ''pins and needles'' and ''itching'' on a 5-point scale (from none to weak to moderate to strong or extremely strong) were included.…”
Section: Paresthesia Symptoms Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow release BA was not available, therefore four grams of BA or placebo was split in to three separate doses per day to minimise the paraesthesia associated with BA consumption above 800 mg per dose [9,16] Maltodextrin was chosen due to its close appearance to BA and to remain consistent with BA double-blind randomised and placebo-controlled trials [17][18][19][20]. The dose used in this trial was not considered high enough to elicit a heighted insulin response or elevate fasting blood sugar.…”
Section: Supplementationmentioning
confidence: 99%